Habitando el shock. La experiencia de la casa como fenómeno de impacto - Puppo, María Eugenia (Universidad ORT Uruguay, 2017)
To understand the contemporary house one must relate it to technology. But more than that, it should be related to the complexity and the dynamism that men is currently immersed in. It is therefore essential, to discern how architecture is being reinterpreted in an infinite process of metamorphosis and virtuality.One of the ways the house materializes in contemporary architecture is translated in the concept of shock. As a result, this architecture is born as a fleeting moment in the mutation of the house. It seems to explore the experience of the inhabitant in them, through the contradiction of shapes, scales and spaces.